Recent Taxonomic Notes and New Distribution Localities of Podocarpus Pers. Species in the Philippines - Salvaña, Florence Roy P; Gruezo, Willian Sm; Hadsall, Annalee S (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2018)
The taxonomy of plants provides a great contribution to understanding diversity and conservation. This study provides additional taxonomic notes on Podocarpus species in the Philippines using newly collected specimens to determine new distribution localities of these species. This study recognises ten species of Podocarpus in the Philippines. Notable results of this study are: (1) the existence of variable leaf forms in P. pilgeri Foxw. correlated to the type of habitat where the species occurs; (2) variable leaf forms and sizes observed in mature and juvenile leaves of all species; (3) support of the sectional arrangement of P. palawanensis de Laub. & Silba; (4) differences between the wild and cultivated representatives of P. costalis C.Presl based on leaf characters; (5) new distributions for P. ramosii R.R.Mill, P. pilgeri, P. costalis, P. neriifolius D.Don, P. rumphii Blume and P. polystachyus R.Br.; (5) no support for the inclusion of P. neglectus Blume and P. hookeri de Laub. as new species found in the Philippines; and (6) comprehensive examination and identification of numerous herbarium specimens and recently collected material.